The impact of relational value towards customer brand relationship stickiness in the context of Malaysia Public higher education service - Hashim, Sharizal; Yassin. M, Norjaya (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study attempts to investigate the effects of customer value specifically the relational value towards customer brand relationship stickiness in Malaysian public higher education service. Investigating relational value is crucial because it has transpired as one of the basic operant resources of customer value in the service co-creation and contributed in the success of customer brand relationship. Using proportionate stratified random sampling, questionnaires were distributed to 701 postgraduate students studying in the Business and Social Science fields in the Malaysian public universities. The reliability of all the constructs tested produced satisfactory coefficients. Multiple regression and Partial Least Square (PLS) bootstrapping procedures were conducted. The findings support the Social Exchange Theory and previous body of research that indicate positive and significant relationships between customer value such as utility value, hedonic value and relational value including customer brand relationship stickiness pertinent to brand relationship quality and brand resonance. In addition, customer relationship stickiness with the service brand is largely dependent on the motivation of exchanging relational values compared to other customer value dimensions such as utility value and hedonic value. This indicates that relational values such as trust, bonding, empathy and mutual dependence are the key elements in the branding process of the service organisation. For this reason, the success of a service can only be achieved through a strong relationship between customers and the brand of the service. Therefore, this paper offers evidence of the association concerning relationship perspective in the social exchange theory. The contribution of this study is an effort to expand customer brand relationship knowledge particularly in the service domain.